2022
DOI: 10.31186/jagrisep.21.1.1-12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Consumer Knowledge and Fresh Cow Milk Consumption in West Sumatera

Abstract: Consumer knowledge builds a consumer perception. This perception can influence consumer preferences and behavior. Previous research has explained the relationship between consumer knowledge and consumption, primarily focusing on product knowledge. In contrast, consumer knowledge is not only about products knowledge but also purchasing and usage knowledge. This study aims to identify consumer knowledge about the product, purchase, and usage of fresh cow milk and analyze its relationship with the level of consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In contrast, a questionnaire performed in west Sumatera revealed that the level of knowledge about the benefits of fresh cow milk is poor, but the knowledge is higher in aspects related to purchasing and usage. Moreover, fresh cow milk consumption depends on consumer product knowledge [58].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a questionnaire performed in west Sumatera revealed that the level of knowledge about the benefits of fresh cow milk is poor, but the knowledge is higher in aspects related to purchasing and usage. Moreover, fresh cow milk consumption depends on consumer product knowledge [58].…”
Section: Discussionmentioning
confidence: 99%